Long-term survival and return to work after refractory out-of-hospital cardiac arrest managed with extracorporeal cardiopul-monary resuscitation; a nationwide follow-up study. (3rd May 2023) - Gregers, E; Kragholm, K; Moerk, S R; Linde, L; Boending, J A; Terkelsen, C J; Lassen, J F; Moeller, J E; Laugesen, H; Smerup, M; Kjaergaard, J; Moeller-Soerensen, P H; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Rigshospitalets and Odense Universitetshospitals common foundation Background: Survival after refractory out-of-hospital cardiac arrest (OHCA) is low. Extracorporeal cardiopulmonary resuscitation (ECPR) is increasingly used for selected patients aiming to increase survival after refractory OHCA. However, ECPR is resource heavy and carries risk of poor functional status. Previous studies have shown favorable neurological outcome in the majority of survivors of OHCA managed with ECPR; yet the share of patients able to return to work has not previously been explored. Purpose: The purpose of this study is to investigate the fraction of patients returning to work after OHCA managed with ECPR in a national cohort of refractory OHCA-patients. Methods: Of about 44, 000 OHCAs during the period of 2011-2020, this nationwide registry-based study included 812 refractory OHCA-patients in the working age between 18 years and 65 years (as 65 was the current age of retirement) who were in employment prior to the event. We excluded 113 ECPR-patients and 3, 536 refractory OHCA-patients managed with standard advanced cardiac life support (sACLS) due to age or unemployment. We defined refractory OHCA as patients with OHCA brought to hospital with on-going CPR. Information on demographics, OHCA circumstances, status at hospital arrival, and survival were retrieved through the Danish Cardiac Arrest Register. Employment status were retrieved through the Danish Research Institute for Economic Analysis and Modelling database. Maintenance of work was defined as return to work without any sick leave relapse (>4 weeks) during six months of employment. Results: Of 812 included refractory OHCA-patients, 137 patients received ECPR while 675 were managed with sACLS. ECPR-patients were slightly younger than sACLS-patients (median 51 vs. 53 years), a higher percentage male sex (84% vs. 79%), and more had favorable OHCA circumstances (witnessed arrest [80% vs. 64%], bystander CPR [75% vs. 67%], and shockable presenting rhythm [59% vs. 37%]). One-year survival was higher for ECPR-patients compared with sACLS-patients (24% vs. 7%, p<0.001). Of one-year survivors, less ECPR-patients were in employment one year after OHCA compared with sACLS-patients (48% vs. 77%, p=0.01). No difference in maintenance of work were found between ECPR- and sACLS-patients after OHCA (88% vs. 79%, p=0.7). Conclusion: Survival was higher for refractory OHCA-patients receiving ECPR- compared to sACLS-therapy, which may reflect selection bias. One out of two ECPR patients returned to work and the majority maintained employment for at least six months. More sACLS-survivors returned to work compared with ECPR-survivors likely reflecting survival bias.